A Vitronectin-Derived Bioactive Peptide Improves Bone Healing Capacity of SLA Titanium Surfaces - Cho, Chang-Bin (Materials (Basel), 2019)
In this study, we evaluated early bone responses to a vitronectin-derived, minimal core bioactive peptide, RVYFFKGKQYWE motif (VnP-16), both in vitro and in vivo, when the peptide was treated on sandblasted, large-grit, acid-etched (SLA) titanium surfaces. Four surface types of titanium discs and of titanium screw-shaped implants were prepared: control, SLA, scrambled peptide-treated, and VnP-16-treated surfaces. Cellular responses, such as attachment, spreading, migration, and viability of human osteoblast-like HOS and MG63 cells were evaluated in vitro on the titanium discs. Using the rabbit tibia model with the split plot design, the implants were inserted into the tibiae of four New Zealand white rabbits. After two weeks of implant insertion, the rabbits were sacrificed, the undecalcified specimens were prepared for light microscopy, and the histomorphometric data were measured. Analysis of variance tests were used for the quantitative evaluations in this study. VnP-16 was non-cytotoxic and promoted attachment and spreading of the human osteoblast-like cells. The VnP-16-treated SLA implants showed no antigenic activities at the interfaces between the bones and the implants and indicated excellent bone-to-implant contact ratios, the means of which were significantly higher than those in the SP-treated implants. VnP-16 reinforces the osteogenic potential of the SLA titanium dental implant.